Orbital box osteotomy in frontonasal dysplasia with severe hypertelorism: Our first experience - I Made Suka Adnyana; Gede Wara Samsarga; Rachel Vania (Wolters Kluwer Medknow Publications, 2023)
Frontonasal dysplasia (FND) is a rare craniofacial deformity, including severe hypertelorism. We herein presented the case of a 6-year-old female patient with FND and Grade III hypertelorism who underwent a four-wall-orbital box osteotomy with a bicoronal approach. Orbital wall osteotomy was performed behind the lacrimal fossa. Central resection was done to allow for medial translocation of the orbits. At the last, the newly positioned orbitals were fixated using wire, absorbable plates, and screws. Neurosurgical assistance with the frontal bone flap before orbital osteotomy helps to leave the cribriform plate intact to preserve the olfactory. Finally, excessive median soft tissue was excised. The patient's hypertelorism improved after surgery. Careful surgical procedures to correct the soft and bony tissue are beneficial treatments for improving the quality of life and general condition of patients with hypertelorism.